Effects and the action mechanism of worker bee pupa and its extract on chronic inflammation and immuno-inflammation - HU Fu-liang; ZHU Wei; CHEN Min-li; ZHENG Huo-qing; LI Ming-yao (浙江大学学报. 农业与生命科学版, 2005)
To elacidate the action mechanism of worker bee pupae (WBP) on chronic inflammation and immuoiflammation, effect of WBP and its water extract and ether extract on granuloma mouse, complete Freund's adjuvant induced arthritis rats and Vit C and cholesterol content in normal adrenal glands of rats were examined. The results showed that WBP and its water extract at medium and high dosage produced a prominent inhibitory effect on granuloma in mouse, brought about antagonism against primary and secondary lesion in arthritis rats significantly, restrained increase in amount of IL-6 and PGE2, prevented decrease in body weight of rats in the course of establishing model, changed the level of Vitamin C and cholesterol in normal adrenal glands of rats distinctly, and index of thymus, adrenal glands were not affected apparently; effect of ether extraction of WBP was less remarkable than that of WBP and its water extract. Therefore, the active ingredients of WBP were believed to be water soluble and enter into water extract. The anti-inflammatory effect seemed to be produced through their influence on adrenal cortex system. Inhibition of activation and differentiation of mononuclear phagocyte as well as increase inflammatory medium may be one of the possible action mechanisms of immune-regulation and anti-inflammatory action of WBP.